EVALUATION OF MEMORIES LEARNING PROGRAM AL-QUR'AN AS A LOCAL CURRICULUM AT MTs.N 7 MODUR JAKARTA TIMUR (Evaluative Research Using CSE-UCLA Models) - Wildani Hidayati (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2018)
Abstract This study aims to find out how effective the implementation of Qur'anic learning in MTs.N 7 East Jakarta models. This study is classified as evaluative research using the CSE-UCLA model consisting of assessment, program planning, implementation programs, programs improvement and program certification. The subject of this study consisted of: school principal, mentor, student and student guardian. Data collection methods are carried out with questionnaires, observation, interviews, and documentation. Data analysis techniques in this study are the Miles and Huburmen models. The activity in data analysis is data reduction , data display (data presentation), and conclusion drawing / verification (drawing conclusions / verification). The research findings show that the Al-Qur'an learning program has been running effectively even though there are obstacles that need to be corrected